Use lean performance measures to achieve customer satisfaction (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The use of performance measures modern and sophisticated one of the most important factors that help organization management in achieving customer satisfaction which today is the premise of The scales cell performance and value stream performance measures that will help organization management elimination of waste in all its forms, by allowing the organization opportunities and strengths to help them in achieving their goals. as well as achieving market share and growth in sales and increase cash inflows Where research deals with the concept of lean performance and managerial and its measurement and the evolution of these measure, and the ability of these organizations to achieve customer satisfaction through the application of these modern measure.